Pengaruh Rasio Likuiditas, Risiko Kredit, Good Corporate Governance, dan Leverage Terhadap Financial Distress - Gunawan Aji; Dwi Maisaroh; Robiatul Adawiyah; Amelia Sya; A’inin Ni’mah (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
High levels of openness and responsibility in business operations constitute excellent corporate governance. Companies can reduce the likelihood of engaging in harmful behaviors and the danger of financial difficulty by adopting a policy of strong corporate governance. The methodology of this study is quantitative descriptive research. Researchers frequently use quantitative descriptive research methodologies to describe or explain phenomena or features of a population or sample. This study discovered that financial hardship is negatively impacted by the factors leverage, credit risk, liquidity ratios, and good corporate governance. Liquidity, as determined by the Current Ratio, is inversely correlated with the severity of financial crises. Therefore, the results of this study support the claim that CR lessens financial stress.